Agricultural growth and climate resilience in the Philippines: Subnational impacts of selected investment strategies and policies - Thomas, Timothy S.; Pradesha, Angga; Perez, Nicostrato D. (International Food Policy Research Institute, 2015)
Being a nation of many islands spanning a consider-able range of latitudes, the Philippines is noted for its climatic and ecological diversity. Significant climate differences exist, not least due to the country’s exten-sive coastal exposure and mountainous areas. For these reasons, the impacts of climate change on agriculture are likely to differ significantly across the country.